Mixed-Strategy Equilibrium in a Market with Asymmetric Information - Rosenthal, Robert W.; Weiss, Andrew (Review of Economic Studies, 1984)
In the mid-1970s several authors studied models of markets with asymmetric information in which equilibria do not exist. Although those authors focused on models of insurance and education, it was recognized that similar nonexistence problems arise in a wide class of models with asymmetric information. Recently, Dasgupta and Maskin have demonstrated that for a game-theoretic version of at least one of those models, although no equilibria may exist in pure strategies, equilibria exist in mixed strategies. In the present paper we construct a mixed-strategy equilibrium for one member of the class—Spence's signalling model of education. Qualitative features of the equilibrium are explored.